2018
DOI: 10.3389/fpsyg.2018.01596
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic Personality Traits Scale (PPTS): Construct Validity of the Instrument in a Sample of U.S. Prisoners

Abstract: The Psychopathic Personality Traits Scale (PPTS; Boduszek et al., 2016) is a personality-based psychopathy assessment tool consisting of four subscales: affective responsiveness, cognitive responsiveness, interpersonal manipulation, and egocentricity. Although the measure offers a promising alternative to other, more behaviorally weighted scales, to date the factor structure of the PPTS and differential predictive validity of its dimensions has only been tested in one study. Consequently, the objective of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
6

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
2
7
0
6
Order By: Relevance
“…While in the first step of the factor analysis, the initial model with 23 items showed inadequate model fit and some critically low factor loadings, the model fit of the 18-item version was acceptable, with moderate to high factor loadings on all four subscales. Its model fit indices are in line with other measurement scales evaluated using CFA (e.g., Boduszek et al, 2018;Hooker et al, 2019). Somewhat lower but still acceptable factor loadings between 0.40 and 0.50 were observed for three items in the Dominating behaviors subscale, which also had the lowest Cronbach's alpha coefficient (α = 0.65).…”
Section: Discussionsupporting
confidence: 78%
“…While in the first step of the factor analysis, the initial model with 23 items showed inadequate model fit and some critically low factor loadings, the model fit of the 18-item version was acceptable, with moderate to high factor loadings on all four subscales. Its model fit indices are in line with other measurement scales evaluated using CFA (e.g., Boduszek et al, 2018;Hooker et al, 2019). Somewhat lower but still acceptable factor loadings between 0.40 and 0.50 were observed for three items in the Dominating behaviors subscale, which also had the lowest Cronbach's alpha coefficient (α = 0.65).…”
Section: Discussionsupporting
confidence: 78%
“…However, a qualitative review suggests the findings were again mixed. In some studies, only a single facet predicted IPV (Boduszek et al, 2018; Cunha et al, 2018; Iyican & Babcock, 2018), while in other studies either multiple or all facets predicted IPV (Hoffmann & Verona, 2018; Stanford et al, 2008; Swogger et al, 2007; Thomson et al, 2019), after controlling for other risk factors. For example, in a study of adult men with a history of IPV, only the affective facet, as measured by the PCL-R, predicted IPV when controlling for previous IPV convictions, previous convictions for non-IPV crimes, and number of incarcerations (Cunha et al, 2018).…”
Section: Resultsmentioning
confidence: 98%
“…In a separate study 90 , which used a different Likert scale, psychopathy levels on the Dirty Dozen were also significantly higher among an incarcerated population compared to a community sample. The PPTS was designed to measure psychopathic personality regardless of respondents' criminal history, but was initially measured in two incarcerated samples 81 , 91 . In this case, the levels in these previous studies were quite similar to those reported here.…”
Section: Discussionmentioning
confidence: 99%